Peningkatan Pemahaman Konsep Matematika melalui Penerapan Model Discovery Learning Berbantuan Microsite S.id pada Murid SMP - Sanjaya, Nanik Fatmawati Sri; Surawan (Jurnal PEKA (Pendidikan Matematika), 2026)
This study examined the improvement of students' mathematical concept understanding through the Discovery Learning model assisted by Microsite S.id. Employing Classroom Action Research (CAR) with the Kemmis and McTaggart framework, this study was conducted in two cycles. The subjects were 32 seventh-grade students of Class VII B at SMP Negeri 6 Tuban. Data were collected using a validated mathematical concept mastery test and classroom activity observation sheets, then analyzed quantitatively and descriptively. The results confirmed a consistent increase in conceptual understanding, where the classroom mean score rose from 46.09 (pre-cycle) to 77.81 (cycle I), and reached 91.88 (cycle II). Concurrently, the classical mastery percentage increased significantly from 9.38% (pre-cycle) to 65.63% (cycle I), and successfully achieved 96.88% at the end of cycle II. This cognitive progress was evident in the students' capacity to re-articulate theoretical principles, categorize objects, formulate mathematical representation models, and solve problems. Furthermore, Microsite S.id effectively served as a learning repository that triggered students' autonomous attention during the concept discovery phase. In conclusion, this model-media unification offers an effective pedagogical alternative to optimize mathematical concept understanding, particularly in quadrilateral topics for junior high school students.